Effect of Irrigation using Diluted Winery Wastewater on Vitis vinifera L. cv. Cabernet Sauvignon in a Sandy Alluvial Soil in the Breede River Valley - Vegetative Growth, Yield and Wine Quality - Howell, C.L.; Myburgh, P.A.; Lategan, E.L.; Schoeman, C.; Hoffman, J.E. (South African Journal of Enology and Viticulture, 2016)
Re-use of winery wastewater for irrigation was investigated in a field trial with micro-sprinkler irrigated Cabernet Sauvignon/99Richter in the Breede River Valley region of South Africa. Irrigation with winery wastewater diluted with river water to 100, 250, 500, 1000, 1500, 2000, 2500 and 3000 mg/L chemical oxygen demand (COD) was compared to irrigation with river water. Under the prevailing conditions, plant water status did not respond to irrigation using diluted winery wastewater. Leaf and shoot element contents did not respond consistently to irrigation using diluted winery wastewater. There were no differences in vegetative growth or yield or juice characteristics, with the exception of juice pH. Consequently, water use and water status of the grapevines were also not affected. Results indicated that a summer interception crop may increase the evapotranspiration of vineyards substantially. Irrigation of grapevines using diluted winery wastewater did not have detrimental effects on wine colour and sensory wine characteristics. The grapevines did not respond to level of COD per se. This indicated that sufficient aeration occurred between irrigations which allowed organic carbon breakdown. The low salinity and sodicity levels in the diluted winery wastewater could be a further explanation why the grapevines did not respond to the wastewater irrigation. In heavier soils, regions with lower winter rainfall, situations where the winery wastewater contains more potassium or where no interception crop is cultivated during summer, grapevine responses may be more pronounced.